Comparative characteristics of sterically hindered phenols and nitroxide radicals as stabilizers of polyethylene photodegradation - I. Yu. Zhukova; I. I. Kashparov; S. V. Kucherenko; E. Sh. Kagan (Advanced Engineering Research)
Introduction. Polymeric materials (PM) are increasingly used in various industries and agriculture. Under the action of UV light, PM are destroyed. UV stabilizers are used to protect PM from photodegradation. Their action is based on the absorption of the photoactive sunlight component or on the deactivation of excited molecules that have already absorbed a light quantum, as well as on the inhibition of dark light-induced reactions. The work objective is to provide a comparative analysis of compounds of the sterically hindered phenols (SHP) series and nitroxide radicals (NR) as the PM photodegradation inhibitors.Materials and Methods. Reagents of the “purum” grade, LDPE premium grade 15803-020 polyethylene film were used for the investigations. The stabilizer was applied to the film by dipping. Carbonyl groups in polyethylene were determined by IR spectroscopy. IR spectra were recorded on Varian-640 instrument.Research Results. 2,4,6-tri-tert-amylphenol (1), 2-methyl-4,6-di-tert-butylphenol         (2),         4-acetylamino-2,2,6,6-tetramethylpiperidin-1-oxyl (3), 3-carboxamido-2,2,5,5-tetramethylpyrrolin-1-oxyl (4) were tested as stabilizers for photo-oxidative degradation of polyethylene. It is known that the accumulation of carbonyl and hydroxyl groups is recorded in PM samples under irradiation in the process of photodegradation through the IR spectroscopy. The absorption band of the carbonyl group at 1720 cm- 1 appears in the IR spectra of oxidized polyethylene. The IR spectra analysis shows that the content of carbonyl groups in the check samples is significantly higher than in the samples treated by stabilizer solutions.Discussion and Conclusions. The experiments show that ni-troxide radicals of 3-carboxamido-2,2,5,5-tetramethylpyrrolin-1-oxyl series and 4-acetylamino-2,2,6,6-tetramethylpiperidin-1-oxyl are the best photostabilizers of polyethylene. Moreover, there is no significant difference between the radicals of the 2,2,6,6-tetramethylpiperidine and 2,2,5,5-tetramethylpyrroline series. Sterically hindered phenols, under photodegradation, have a far smaller stabilizing effect, falling short of nitroxide radicals.